Verbal Violence in the Press: A Case Study of Persian Newspapers - Mohammad RasekhMahand; Mojtaba AlizadeSahraii; Raheleh Izadifar; Roghayyeh salimiyan (مطالعات زبانی و بلاغی)
One of the important functions of language is conveying each person’s emotions to another people. Emotions are abstract concepts that should be converted into concrete concepts in order to become comprehensible; Metaphors and adjectives are common tools for changing abstract concepts to concrete ones. In this study we try to answer the following question: “Has the Persian language changed regarding to the use of violent verbal tools?” In order to answer this question, we have to understand if the mental and cognitive representation of anger in language has had an ascending development or a descending one? One of the representations of expressing emotions such as anger in everyday language is through the daily newspapers published in that language. In other words, the text of a newspapers reflects the thoughts and speeches of that society. Thus, the study of anger in this research has been limited to the metaphors representing anger in Persian and also the adjectives that using this emotion in a corpus consisting of Persian newspapers. This paper is based on the theory of conventional metaphors in such important papers as Lakoff and Johnson 1980 and Lakoff 1993. The metaphors are recognized here according to the Metaphor Identification Process (MIP) in Pragglejaz (2007). In sum, 100 editorial or leading articles, 2 important and bestselling newspapers, namely ‘Keyhan’ and ‘Ettelaat’ which have an archive of at least 50 years (50 of each newspaper and 1 of each year) were chosen randomly for this research and 18 source domains were identified for the metaphors. The importance of this study is that, it reveals the changes in using violence in Persian according to a natural and real corpus of popular newspapers published in Persian, and also shows its relationship with the important social and political changes of each decade. This way, a cognitive pattern of Persian based on the development of violence change in this language and its representation in Persian newspapers will be achieved. The results of this study shows that the political and social factors have been influential in the development of violence change in Persian newspapers.